Understanding of the Concept of Total Pain: A Prerequisite for Pain Control - Mehta, Anita; Chan, Lisa S. (Journal of Hospice and Palliative Nursing, 2008)
Pain is one of the most common and distressing symptoms described by palliative cancer patients. Despite the fact that pain can be controlled, poor pain relief continues to be a challenge in palliative care. The lack of clarity in how to understand pain for this population contributes to the persistence of poor pain management. Dame Cicely Saunders coined the term ‘‘total pain’’ to characterize the multidimensional nature of the palliative patient’s pain experience to include the physical, psychological, social, and spiritual domains. This article highlights the use of the concept of ‘‘total pain’’ in the assessment and management of pain for cancer patients who are dying and presents a case study to illustrate that optimal pain relief is not possible if all dimensions of ‘‘total pain’’ are not addressed. Nursing implications for clinical practice are discussed. The concept of ‘‘total pain’’ should be the driving force leading to the standardization of pain definition, intervention, and evaluation for palliative cancer patients.